LAYANAN KONSELING KELOMPOK MELALUI ZOOM MEETING DENGAN TEKNIK CINEMATHERAPHY TERHADAP MOTIVASI BELAJAR KELAS XI - Rini Nuraeni; Heris Hendriana; Ardian Renata Manuardi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
The purpose of this study is to find out the implementation, response of teachers and students, difficulties, and the impact of the implementation of group counseling services through Zoom Meeting with cinematheraphy techniques on the motivation of learning students of grade XI SMA Dar El-Fikri Cianjur. Research uses techniques by taking data through observations and interviews. Interviews were conducted to counseling guidance teachers, principals, deputy principals, teachers and students. This study found that 1) group counseling services stage formation of the transition stage, the stage of activities and closure and evaluation 2) The response of teachers and students is quite good, very comfortable, enthusiastic in learning, and can support from teachers, 3) Difficulties experienced by students, namely facilities and infrastructure and home conditions; and 4) Obstacles experienced by teachers, namely time, coordination, lack of knowledge of BK teachers, infrastructure facilities.Keywords: Cinematheraphy, Counseling, Motivational Learning